Ru(II) Complexes with 3,4-Dimethylphenylhydrazine: Exploring In Vitro Anticancer Activity and Protein Affinities - Jasmina Dimitrić Marković; Dušan Dimić; Thomas Eichhorn; Dejan Milenković; Aleksandra Pavićević; Dragoslava Đikić; Emilija Živković; Vladan Čokić; Tobias Rüffer; Goran N. Kaluđerović (Biomolecules)
Two new Ru(II) complexes, mononuclear [RuCl2(η6-p-cymene)(3,4-dmph-κN)] (1) and the binuclear complex [{RuCl(η6-p-cymene)}2(μ-Cl)(μ-3,4-dmph-κ2N,N′)]Cl (2; 3,4-dmph = 3,4-dimethylphenylhydrazine), are synthesized and experimentally and theoretically structurally characterized utilizing 1H and 13C NMR and FTIR spectroscopy, as well as DFT calculations. Degradation product of 2, thus ([{RuCl(η6-p-cymene)}2(μ-Cl)(μ-3,4-dmph-κ2N,N′)][RuCl3(η6-p-cymene)] (2b) was characterized with SC-XRD. In the crystals of 2b, the cationic and anionic parts interact through N-H...Cl hydrogen bridges. The spectrofluorimetric measurements proved the spontaneity of the binding processes of both complexes and HSA. Spin probing EPR measurements implied that 1 and 2 decreased the amount of bound 16-doxylstearate and implicated their potential to bind to HSA more strongly than the spin probe. The cytotoxicity assessment of both complexes against the MDA-MB-231 and MIA PaCa-2 cancer cell lines demonstrated a clear dose-dependent decrease in cell viability and no effect on healthy HS-5 cells. Determination of the malondialdehyde and protein carbonyl concentrations indicated that new complexes could offer protective antioxidant benefits in specific cancer contexts. Gel electrophoresis measurements showed the reduction in MMP9 activity and indicated the potential of 1 in limiting the cancer cells’ invasion. The annexin V/PI apoptotic assay results showed that 1 and 2 exhibit different selectivity towards MIA PaCa-2 and MDA-MB-231 cancer cells. A comparative molecular docking analysis of protein binding, specifically targeting acetylcholinesterase (ACHE), matrix metalloproteinase-9 (MMP-9), and human serum albumin (HSA), demonstrated distinct binding interactions for each complex.